An Innovative Approach to a Hybrid Quadrotor Design - Haidar Fadhil AL-Qrimli; Leroy D’souza; Omar Dhari Hussein (Universitas Muhammadiyah Yogyakarta, 2021)
This article presents a hybrid design for a quadrotor aircraft. The hybrid is a combined system of a land robot and a quadrotor aircraft aimed at performing both driving and flying tasks. The hybrid quadrotor performs flying tasks in the usual way a normal quadrotor would do while the added caterpillar tracks would help maneuver over any type of terrain. The current prototype design was established after analyzing multiple designs and their response to various loads and impact forces. This study focuses on a practical approach to designing a hybrid quadrotor with experimental studies demonstrating the performance and feasibility on both flying and driving missions. The research outcomes were successful, and the new hybrid structure managed to survive a drop from a height greater than 2 meters. The hybrid quadrotor prototype was tested using finite element analysis and validated experimentally.